Global business models mapping: the American and European models - Lopes da Costa, R.; Nelson António (XXVII Jornadas Hispano-Lusas. Alicante 2017, 2017)
The globalization of business markets requires rethinking existing management theories, and demands a global mental map, open to cultural diversity. The direct competitor, once across the street, might now be kilometres away, putting pressure on companies to continuously learning, developing their competencies and updating their knowledge. This refers not only to practical and technical knowledge, but also to a wide-reaching knowledge of cultures and markets, be they strong, emerging or weak. As such, this article seeks to present theoretical guidance on the manner in which managers “think strategy” in two very different contexts – those of the US and Germany. Management models for each, related to their specific cultural characteristics, are presented; and the implications of each considered.